The researches of kinetic electron emission for creation of new-type current source - Balebanov, V.M.; Zhurenko, V.P.; Karas, V.I.; Karas, I.V.; Kononenko, S.I.; Moiseev, S.S.; Muratov, V.I. (Вопросы атомной науки и техники, 2000)
It is suggested that the high energy electrons produced in ionization due to the nuclear particle flow should be used for effective conversion the radioactive decay energy into electrical energy. The conversation of secondary electron emission energy enables one to create a power source with a typical voltage of (10-20) V and a capacity above 2000 KWt×h/kg, this being much higher than for common sources. Moreover, the operation of this type of sources does not require heating to high temperature and use of a refrigerator; this significantly extends their area of application. The experimental studies into secondary emission characteristics of various materials were carried out to optimize binary cell materials of a secondary - emission radioisotope current source. The total current as a function of collector materials was measured. New data on the secondary emission characteristics of certain materials were obtained. It was ascertained that the total binary cell current had an effect upon secondary electron - electron emission. By way of example, a typical power dependence of voltage was investigated for copper collector; the optimum voltage value corresponding to peak power was calculated too.